In Vitro Assessment of Some Brands of Fluconazole Capsules Marketed in Port Harcourt, Nigeria - Nkemakolam, Nwachukwu; C, Ugoeze Kenneth; Oluigbo, Kennedy Emeka (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: A routine in vitro pharmacopeial quality assessment of five brands of fluconazole capsules with label claims of 50.0 mg marketed in Port Harcourt, Nigeria was carried out to ascertain their consistencies. Methods: The brands were procured from various pharmacies in Port Harcourt and coded Fluco-A, Fluco-B, Fluco-C, Fluco-D and Fluco-E. Visual assessments of the samples were carried out besides in vitro quality considerations such as identification of the active pharmaceutical ingredient (API), capsules uniformity of weight, disintegration, an assay of the total content of fluconazole and dissolution studies. Results: Each brand contained fluconazole with relevant product packet information uncompromisingly conspicuous.The label claims for fluconazole contents were satisfactory. The weight variation of the capsulesacross the brands were between 170.25 mg ± 2.25% -333.14 mg ± 1.50 %. Each brand disintegrated within 10 min. Total drug content was within 88.43 ± 0.12% to 102.96 ± 0.53 %.Above 80.0% of fluconazole was released within 30.0 min in the release studies of the respective brands. Conclusion: The results obtained for the capsules uniformity of weight, disintegration time, the total content of the API and the drug release profiles were within acceptable limits of the United States Pharmacopoeia (USP).